2005
DOI: 10.1093/humrep/dei184
|View full text |Cite
|
Sign up to set email alerts
|

A prospective, longitudinal study of the renin–angiotensin system, prostacyclin and thromboxane in the first trimester of normal human pregnancy: association with birthweight

Abstract: Angiotensinogen is known to be rate-limiting in pregnancy. Its association with birthweight may be through effects on early plasma volume expansion and may have implications for intrauterine growth restriction and pre-eclampsia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…If this occurs, thrombosis, fibrinoid necrosis, and atherosclerosis may be seen in the placenta and decidual vessels and can cause spontaneous abortion, preterm delivery, fetal distress, preeclampsia, and fetal growth restriction [10][11][12][13][14]. Studies of fetal growth restriction and preeclampsia performed with blood samples have reported an increase in TXB2 levels [15][16][17][18][19]. However, others believe that TXB2 does not change much during pregnancy [20].…”
Section: Discussionmentioning
confidence: 99%
“…If this occurs, thrombosis, fibrinoid necrosis, and atherosclerosis may be seen in the placenta and decidual vessels and can cause spontaneous abortion, preterm delivery, fetal distress, preeclampsia, and fetal growth restriction [10][11][12][13][14]. Studies of fetal growth restriction and preeclampsia performed with blood samples have reported an increase in TXB2 levels [15][16][17][18][19]. However, others believe that TXB2 does not change much during pregnancy [20].…”
Section: Discussionmentioning
confidence: 99%
“…During the early stages of normal pregnancy, activation of the local RAS (31,32) and systemic RAS (33,34) exists. At 3-6 gestational weeks, plasma prorenin levels increase 10-fold, with much lower prorenin levels from 9 weeks onward (31).…”
Section: Pre-eclampsia and The Rasmentioning
confidence: 99%
“…BP increased by approximately 8.3 mmHg per Ang-N gene copy [11,25]. During human pregnancy, plasma Ang-N levels may increase more than 10-fold [26]. The use of oral estrogens may increase Ang-N levels more than 4-fold and systolic BP up to 15 mm Hg [6,8,9,27].…”
Section: Discussionmentioning
confidence: 99%
“…In terms of physiological usefulness, the activation of the renin-angiotensin system by high plasma Ang-N may be a helpful mechanism to compensate for the increased circulatory demands for instance during pregnancy [26]. In situations with exogenous stimulation of plasma Ang-N levels for example by the use of oral contraceptives, such an activation may instead lead to an unwanted BP increase.…”
Section: Discussionmentioning
confidence: 99%